Event-Related Potentials and Emotion Processing in Child Psychopathology - Chronaki, Georgia (Frontiers in Psychology, 2016)
In recent years there has been increasing interest in the neural mechanisms underlying altered emotional processes in children and adolescents with psychopathology. This review provides a brief overview of the most up-to-date findings in the field of Event-Related Potentials (ERPs) to facial and vocal emotional expressions in the most common child psychopathological conditions. In regards to externalising behaviour (i.e. ADHD, CD), ERP studies show enhanced early components to anger, reflecting enhanced sensory processing, followed by reductions in later components to anger, reflecting reduced cognitive-evaluative processing. In regards to internalising behaviour, research supports models of increased processing of threat stimuli especially at later more elaborate and effortful stages. Finally, in autism spectrum disorders abnormalities have been observed at early visual-perceptual stages of processing. An affective neuroscience framework for understanding child psychopathology can be valuable in elucidating underlying mechanisms and inform preventive intervention.